Primary Seminal Vesicle Clear Cell Adenocarcinoma: A Rare Entity - Jitin Goyal; Rupinder Singh Baweja; Nitin Agarwal; Anila Sharma; Sunil Kumar Puri (Indian Journal of Medical and Paediatric Oncology)
Primary seminal vesicle cancer (SVC) is an exceptionally rare occurrence and is often secondary to bladder or prostate cancers. Adenocarcinoma is being the predominant histological type, with only a few cases reported in the literature.